1994
DOI: 10.1177/155005949402500110
|View full text |Cite
|
Sign up to set email alerts
|

Lower Interhemispheric Coherence in a Case of Agenesis of the Corpus Callosum

Abstract: Interhemispheric coherence and relative power were compared in a patient with total agenesis of the corpus callosum and age and sex matched controls. The patient showed lower interhemispheric coherence than normal controls in F3-F4, C3-C4, and in P3-P4 especially in the higher theta, lower alpha, and beta bands. Differences in relative power were much less marked. These results seem to reflect that interhemispheric connection is degraded because of callosal agenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
1
10
0
3
Order By: Relevance
“…An fMRI case study of three individuals with AgCC demonstrated reduced functional connectivity in regions serving auditory, motor and language processing, although with such a small sample size, the statistical significance of this reduced connectivity was difficult to determine [73]. In EEG, reductions in resting-state alpha coherence have been repeatedly reported in individuals with AgCC, generally between frontal and central scalp electrodes [72], [75][76]. The precision of source localization inherent to MEG-I analyses used in the present study allows us to target which brain areas are specifically underconnected in callosal dysgenesis, a step far beyond the limitations of EEG spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…An fMRI case study of three individuals with AgCC demonstrated reduced functional connectivity in regions serving auditory, motor and language processing, although with such a small sample size, the statistical significance of this reduced connectivity was difficult to determine [73]. In EEG, reductions in resting-state alpha coherence have been repeatedly reported in individuals with AgCC, generally between frontal and central scalp electrodes [72], [75][76]. The precision of source localization inherent to MEG-I analyses used in the present study allows us to target which brain areas are specifically underconnected in callosal dysgenesis, a step far beyond the limitations of EEG spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by electrophysiological studies reporting decreased interhemispheric coupling in patients with callosal agenesis [Brown et al, 1998; Koeda et al, 1999; Nagase et al, 1994; van de Wassenberg et al, 2008] and reduced resting state functional connectivity following callosal transection [Johnston et al, 2008]. In multiple sclerosis (MS), an inflammatory, demyelinating disorder of the nervous system, focal lesions within the CC and Wallerian degeneration from adjacent hemispheric white matter lesions are thought to result in atrophy of the CC [Klawiter et al, 2015].…”
Section: Introductionmentioning
confidence: 92%
“…In many cases, EEG functional connectivity has been shown to reflect the underlying structural properties of the brain. For example, coherence between electrodes placed on each hemisphere is weakened in individuals with surgically sectioned or underdeveloped commissural white matter fibres (Koeda et al, 1995;Montplaisir et al, 1990;Nagase, Terasaki, Okubo, Matsuura, & Toru, 1994;Nielsen, Montplaisir, & Lassonde, 1993). Furthermore, studies have noted positive correlations between functional EEG coherence and white matter tract integrity in patients with M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%